2011
DOI: 10.1038/hdy.2011.107
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal rearrangements and karyotype evolution in carnivores revealed by chromosome painting

Abstract: Chromosomal evolution in carnivores has been revisited extensively using cross-species chromosome painting. Painting probes derived from flow-sorted chromosomes of the domestic dog, which has one of the most rearranged karyotypes in mammals and the highest dipoid number (2n=78) in carnivores, are a powerful tool in detecting both evolutionary intra- and inter-chromosomal rearrangements. However, only a few comparative maps have been established between dog and other non-Canidae species. Here, we extended cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 42 publications
(159 reference statements)
5
73
1
Order By: Relevance
“…The analysis demonstrates a high degree of karyotype conservation between the raccoon and the cat, as well as a highly rearranged structure of the dog chromosomes. The results are in agreement with prior studies (Nie et al 2012). For this analysis, the cat (GCF_000181335.2), the dog (GCF_000002285.3) and the common raccoon (pl-1k) genome assemblies were aligned using the LastZ alignment algorithm (Robert S. Harris 2007) using "--notransition --step=20 -nogapped" command options; the cat and dog assemblies were used as targets.…”
Section: Figure 1: Juicebox Assembly Tools Module Enables Visualizatisupporting
confidence: 72%
See 1 more Smart Citation
“…The analysis demonstrates a high degree of karyotype conservation between the raccoon and the cat, as well as a highly rearranged structure of the dog chromosomes. The results are in agreement with prior studies (Nie et al 2012). For this analysis, the cat (GCF_000181335.2), the dog (GCF_000002285.3) and the common raccoon (pl-1k) genome assemblies were aligned using the LastZ alignment algorithm (Robert S. Harris 2007) using "--notransition --step=20 -nogapped" command options; the cat and dog assemblies were used as targets.…”
Section: Figure 1: Juicebox Assembly Tools Module Enables Visualizatisupporting
confidence: 72%
“…Here, we show alignment blocks with scores larger than 50,000 (Robert S. Harris 2007), with direct synteny blocks colored red, and inverted blocks colored blue. Chromosome order and orientation of the common raccoon chromosomes has been modified in order to facilitate the comparison with (Nie et al 2012).…”
Section: Figure 1: Juicebox Assembly Tools Module Enables Visualizatimentioning
confidence: 99%
“…Chromosome painting data for the Feliformia and Caniformia branches were recently reviewed [Nie et al, 2012]. A detailed tree depicting chromosomal evolution of both branches of Carnivora was presented in that study.…”
mentioning
confidence: 99%
“…Early karyotype studies of Laurasiatheria have suggested there are significant differences in chromosome number, morphology and banding pattern among the six orders (Ao et al, 2007;Frönicke et al, 1997;Kulemzina et al, 2009;Nie et al, 2011;SoteroCaio et al, 2011;Trifonov et al, 2008;Yang & Graphodatsky, 2004;Yang et al, 2006;Ye et al, 2006). Kulemzina et al (2010) investigated the phylogenetic relationships among Laurasiatheria orders by comparing their karyotypes with human karyotype, and proposed the Laurasiatheria phylogeny as (Eulipotyphla, (Cetartiodactyla, ((Perissodactyla, Chiroptera), (Carnivora, Pholidota)))) ( Figure 1A, Table 1).…”
Section: Laurasiatheria Phylogeny Inferred From Cytogenetic and Morphmentioning
confidence: 99%